LITERATURE REVIEW ON FRACTURE TOUGHNESS AND IMPACT TOUGHNESS - Mr. Shinde S. S; Dr. Dhamejani C. L. (International Journal of Innovations in Engineering Research and Technology, 2021)
The present paper gives a technical review of fracture toughness, and impact toughness for metallic materials in terms of the linear elastic fracture mechanics. This includes the early investigations and recentadvances of fracture toughness test methods and practices developed by various agencies and societies. Thereview describes the mostimportant fracturemechanics parameters: such as the elastic energy release rate G, the stress intensity factor K, the J-integral, thecrack-tip opening displacement (CTOD) and the crack-tip opening angle(CTOA) from the basic concept, definition, to, test methods. Attention is paid to guidelines on how to choose an appropriatefracture parameter to characterize fracture toughness for the material of interest,and how to measure the fracture toughness value defined either at a critical point or ina resistance curve format